The Analysis of Figurative Language in Little Mix’s Third Album Entitled “Get Weird” - Ni Kadek Ayu Prawita; I Gusti Ayu, Vina Widnyana Putri; I Wayan, Juniartha (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2023)
This research aims to identify the kinds of figurative languages used in the chosen song lyrics of Little Mix album entitled "Get Weird" to examine the meanings of figurative languages in the song lyrics of Little Mix. Several song lyrics from Little Mix's album that were taken randomly are the database of this analysis. This study used a qualitative approach and formal and informal methods to describe the types of figurative language. The theory of Perrine (1970) was used to analyse the types of figurative languages, and the theory by Leech (1974) was used to describe the meaning of each type of figurative language. After the study has been finished, the researchers revealed that the chosen song lyrics of Little Mix's album consist of 10 lyrics that used figurative language. In additional to that, six types of figurative language ware found, namely Simile (10%), Personification (10%), Hyperbole (20%), Paradox (20%), Metaphor (30%), and Metonymy (10%).